The equine hospital manual (Blackwell Publishing, 2008)
The must-have resource drawing together all aspects of hospital care of the horse and specialist techniques in equine medicine. Written by a team of over 30 international experts working at the cutting edge of equine medicine and surgery. The emphasis is on practical, easy-to-access information, with a sound basis in evidence based medicine and full references for further enquiry.